Research Progress in the Field of Adsorption and Catalytic Degradation of Sewage by Hydrotalcite‐Derived Materials. Issue 4 (27th August 2019) - Pan, Duo; Ge, Shengsong; Tian, Jiangyang; Shao, Qian; Guo, Lin; Liu, Hu; Wu, Shide; Ding, Tao; Guo, Zhanhu
Abstract: With the rapid development of industry and agriculture and the greatly improved living conditions, the resultant gradually deteriorated environments threaten the human beings. Refractory or even toxic pollutants, which are from different industries such as printing and dyeing, pesticides, chemicals, petrochemicals, plastics and rubber, seriously threat the ecosystems and human health. Having the advantages of flexible composition, unique structure, high stability, memory effect, easy preparation and low cost, hydrotalcite compounds have a great potential in sewage degradation and environmental protection. This study focuses on the adsorption and catalytic properties (such as photocatalysis, electrocatalysis and photoelectrocatalysis) of hydrotalcite‐derived materials for treating organic, inorganic and heavy metal ion sewage. The types of adsorption and catalysis, and the effects of various influencing factors on the degradation efficiency were discussed as well. Abstract : Refractory or even toxic pollutants seriously threat the ecosystems and human health. This article focuses on the adsorption and catalytic properties of hydrotalcite‐derived materials for treating sewage. The types of adsorption and catalysis, and various influencing factors for the sewage treatment are discussed as well.